CrowNet: Open Source Modeling and Simulation of Pedestrian-2-X and Crowd Networks - Schuhback, Stefan; Maria Mayr, Christina; Ott, Jorg; Wischhof, Lars (IEEE access, 2025)
One way to improve urban traffic is by networking road users. While V2X communication initially focused on vehicles, attention is now shifting towards pedestrian communication, particularly through wireless applications. Simulations are crucial for developing and evaluating these applications and their communication protocols, but most existing frameworks are vehicle-centered. Consequently, they lack accurate pedestrian models, limiting their use for analyzing applications for pedestrians. We close this gap by introducing CrowNet, the first open-source co-simulation framework designed explicitly for pedestrian-centric wireless applications. CrowNet couples a high-fidelity pedestrian simulator with wireless network simulations in OMNeT++. The framework is developed systematically, beginning with specifying the scope and software requirements. Co-simulation techniques are used to integrate established state-of-the-art simulators, including OMNeT++ model libraries (INET, Artery, Veins, Simu5G), mobility simulators (SUMO, Vadere), and a pedestrian management simulator. The defining feature of CrowNet is its model library for pedestrian-to-X communication applications - a component that no other open co-simulation framework currently provides. We run simulations to verify the software requirements. Our simulations show that the scientific simulation framework CrowNet is suitable for the simulation of pedestrian-centric applications with high accuracy requirements. We also present examples demonstrating that CrowNet can be applied to a wide range of use cases, including V2X and traffic management applications. We conclude that CrowNet represents a novel and valuable simulation tool for traffic management and pedestrian communication research, filling a critical gap in simulation tools for the assessment of pedestrian-centric applications.